Membangun Moralitas Kajian Semantik Kata Khuluq dalam Al-Qur’an - Iskandar, Iskandar (SUHUF, 2009)
The Qur’an is the main source of the Islamic teachings which has a great interest in particular to produce the correct paradigm for human conduct and act, moral acts which by the Qur’an are considered to be part of ‘ibadah’ or ‘devotion to God’. Therefore, the Qur’an becomes a very important to create a moral order for all the acts of humankind. This writing tries to show some important aspects of Islamic moral being adopted from the Qur’anic guidances which cover moral terminology, source of moral and basic principles of the moral in its attempt to give some contribution for managing the life of humankind.